Giving Voice to the Voiceless? Second Thoughts on Testimony in Transitional Justice - WINTER, FRANKA CATHARINA (North Carolina State University, 2009)
The article discusses the use of testimony as an instrument of transitional justice and the democratic value attributed to this medium. It analyzes its power structures, as well as the economies of speech of public hearings and the implications of truth commissions' claim to give voice to the voiceless. The article also addresses the lack of detailed methodological inquiry into this special genre of speech, and offers some insight into its gains and opportunities for social research.
PUBLISHED
Keywords: testimony; transitional justice